2012
DOI: 10.1111/j.1600-0765.2011.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

The formation of immune complexes is involved in the acute phase of periodontal destruction in rats

Abstract: In the present study, we showed that the formation of immune complex appears to be involved in the acute phase of periodontal destruction and that the biological activity of antigens is also important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 38 publications
1
24
0
1
Order By: Relevance
“…Focusing on the host immune system, especially immune complexes, we recently found, using anti‐C1qB as a marker of immune complexes, that alternate topical applications of lipopolysaccharide (LPS) and anti‐LPS IgG into rat gingival sulcus induced loss of attachment, and we detected immune complexes in the junctional epithelium and adjacent connective tissue, where neutrophils were infiltrating . These findings strongly suggested that the formation of immune complexes accelerates attachment loss by inducing infiltration of neutrophils.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Focusing on the host immune system, especially immune complexes, we recently found, using anti‐C1qB as a marker of immune complexes, that alternate topical applications of lipopolysaccharide (LPS) and anti‐LPS IgG into rat gingival sulcus induced loss of attachment, and we detected immune complexes in the junctional epithelium and adjacent connective tissue, where neutrophils were infiltrating . These findings strongly suggested that the formation of immune complexes accelerates attachment loss by inducing infiltration of neutrophils.…”
mentioning
confidence: 61%
“…In our previous studies , C1qB was stained immunohistologically as a marker of immune complexes. After sections were deparaffinized, endogenous peroxidase activity was blocked with 0.3% H 2 O 2 /methanol for 30 min, followed by incubation in normal goat serum for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In general, to observe immune complexes immunohistologically, antigen and antibody are investigated individually. However, in our serial studies , it was difficult to detect antigens and their specific antibodies immunohistologically. When the classical pathway of complement is activated, the C1 component binds to antigen‐bound antibodies.…”
Section: Methodsmentioning
confidence: 77%
“…Moreover, GA displays anti‐inflammatory activities via inhibition of the classical complement pathway . In a previous study, we reported that the formation of immune complexes is involved in attachment loss in rats . Therefore, we speculated that GA may be useful in controlling periodontitis; however, no reports on the inhibitory effects of GA on gingival attachment loss are available.…”
Section: Introductionmentioning
confidence: 99%